2022
DOI: 10.1177/23337214221144192
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Adverse Incidents Research in Aged Care Homes: Learnings, Gaps, and Challenges

Abstract: Background: Adverse incidents are well studied within acute care settings, less so within aged care homes. The aim of this scoping review was to define the types of adverse incidents studied in aged care homes and highlight strengths, gaps, and challenges of this research. Methods: An expanded definition of adverse incidents including physical, social, and environmental impacts was used in a scoping review based on the PRISMA Extension for Scoping Reviews Checklist. MEDLINE, CINAHL, and EBSCOhost were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…Many aged care services have a limited capacity to offer the care that older people and carers need and want. Internationally, this was demonstrated by reviews that found a high prevalence of elder abuse in institutions (Yon et al, 2019) and a range of adverse incidents in aged care homes, including falls, pressure injuries and loneliness (St Clair et al, 2022). Similarly, in Australia, the Royal Commission into Aged Care Quality and Safety revealed 'many flaws ', with 'substandard care … widespread' (2021, pp.…”
Section: (Diana)mentioning
confidence: 99%
“…Many aged care services have a limited capacity to offer the care that older people and carers need and want. Internationally, this was demonstrated by reviews that found a high prevalence of elder abuse in institutions (Yon et al, 2019) and a range of adverse incidents in aged care homes, including falls, pressure injuries and loneliness (St Clair et al, 2022). Similarly, in Australia, the Royal Commission into Aged Care Quality and Safety revealed 'many flaws ', with 'substandard care … widespread' (2021, pp.…”
Section: (Diana)mentioning
confidence: 99%